A Study on Application-layer Attacks in Communications Network - Arindam Giri, Piyu Sarcar, Mrutyunjay Rout (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Distributed Denial of Service(DDoS) attacks are now a threat to Internet. Though traditionally DDoS attacks stuck at network layer, recently an increasing number of DDoS attacks occur at application layer. They target specific web applications. These attacks appear as legitimate traffic, because of their low and slow rate. In this paper, we introduce DDoS attacks along with taxonomy and method to detect application layer DDoS(App-DDoS) attacks. Recent research trends in application-layer attack detection are also included